Investigations on artificially extending the spectral range of natural vision - Abhijith Krishnan; C. S. Deepak; K. S. Narayan (APL Bioengineering, 2023)
Organic semiconductors are being explored as retinal prosthetics with the prime attributes of bio-compatibility and conformability for seamless integration with the retina. These polymer-based artificial photoreceptor films are self-powered with light-induced signal strength sufficient to elicit neuronal firing events. The molecular aspect of these semiconductors provides wide spectral tunability. Here, we present results from a bulk heterostructure semiconductor blend with a wide spectral response range. This combination elicits clear spiking activity from a developing blind-chick embryonic retina in the subretinal configuration in response to white light. The response is largely triggered by the blue–green spectral regime rather than the red-NIR regime for the present polymer semiconductor layer attributes.